Is team‐based perception of safety in the operating room associated with self‐reported wrong‐site surgery? An exploratory cross‐sectional survey among physicians. Issue 6 (29th May 2018) - Cullati, Stéphane; Courvoisier, Delphine S.; Francis, Patricia; Degiorgi, Adriana; Bezzola, Paula; Licker, Marc‐Joseph; Chopard, Pierre
Abstract: Aims: Participation in wrong‐site surgery may negatively influence the perception of safety by the health care professionals in the operating room (OR). The objective was to explore if perception of safety in the OR was seen as a team‐based or individualist concern and whether having participated in wrong‐site surgery was associated with perception of safety. Method and Results: Cross‐sectional survey at 2 annual meetings of surgery, in Switzerland, 2010. We used multivariate generalized models to assess the association of perception of safety in the OR (1 item) with self‐reported participation in wrong‐site surgery—overall, past (more than 3 y ago), or recent (last 3 y) participations—controlling for sociodemographic characteristics and opinion of the surgical safety checklist. One hundred ninety respondents answered the questionnaire (participation rate of 22.6%). Respondents mostly had a team‐based, rather than an individualistic, perception of safety in the OR. In multivariate analyses, the influence of ever participation in wrong‐site surgery was not significant. However, past participation in wrong‐site surgery (more than 3 y ago) was associated with perception of safety as team based, whereas recent participation (last 3 y) was associated—despite not significant at α ≤ 5%—with perception of safety as individualistic. Conclusion: In this sample, safety in the OR is most often seen as team based rather than individualistic. Perceiving safety in the OR as team based varies according to recent or past participation in wrong‐site surgery. Longitudinal research is needed to assess causality between participation in wrong‐site surgery and change in perception of safety. Abstract : Aims: Participation in wrong‐site surgery may negatively influence the perception of safety by the health care professionals in the operating room (OR). The objective was to explore if perception of safety in the OR was seen as a team‐based or individualist concern and whether having participated in wrong‐site surgery was associated with perception of safety. Method and Results: Cross‐sectional survey at 2 annual meetings of surgery, in Switzerland, 2010. We used multivariate generalized models to assess the association of perception of safety in the OR (1 item) with self‐reported participation in wrong‐site surgery—overall, past (more than 3 y ago), or recent (last 3 y) participations—controlling for sociodemographic characteristics and opinion of the surgical safety checklist. One hundred ninety respondents answered the questionnaire (participation rate of 22.6%). Respondents mostly had a team‐based, rather than an individualistic, perception of safety in the OR. In multivariate analyses, the influence of ever participation in wrong‐site surgery was not significant. However, past participation in wrong‐site surgery (more than 3 y ago) was associated with perception of safety as team based, whereas recent participation (last 3 y) was associated—despite not significant at α ≤ 5%—with perception of safety as individualistic. Conclusion: In this sample, safety in the OR is most often seen as team based rather than individualistic. Perceiving safety in the OR as team based varies according to recent or past participation in wrong‐site surgery. Longitudinal research is needed to assess causality between participation in wrong‐site surgery and change in perception of safety.